Long non-coding RNAs in antiviral immunity. (March 2021) - Vierbuchen, Tim; Fitzgerald, Katherine A.
Abstract: Tight regulation of the immune response is fundamental for efficient pathogen clearance and to prevent excessive inflammation. Long non-coding RNAs (lncRNAs) have emerged as potent regulators of the innate and adaptive immune responses to viral pathogens. Host-derived lncRNAs control the differentiation and polarization of immune cell populations and the production of cytokines, interferons and antiviral factors. This review provides an updated overview of lncRNAs that modulate viral replication or pathogenesis. Beyond that, viruses have developed lncRNA-based strategies to mask themselves from immune detection and evade antiviral immunity. A deeper understanding of lncRNA biology in the context of host-pathogen interactions may unveil new treatment strategies in the near future.